Cult hero [videorecording (DVD)] - Revie, Kevin; Collins, Liv; Barrett, Ryan; Burgess, Tony (Gravitas Ventures, 2023)
A control freak attempts to rescue her husband from a "wellness center" with the help of a Cult Buster.